THE FUTURE OF ARTIFICIAL INTELLIGENCE AND ITS IMPACT ON EMPLOYMENT. - Ibrohimova Mohinur Vohid qizi; Ilxomova Husnida Ilyos qizi (TADQIQOTLAR, 2025)
Abstract. Artificial intelligence (AI) is rapidly advancing, with the potential to transform industries and society as a whole. This thesis explores the future of AI and its impact on employment. By reviewing current trends and examining projections for AI's role in various sectors, the study assesses both the opportunities and challenges AI poses to the workforce. While AI can improve productivity and create new job categories, it also  raises  concerns  about  job  displacement  and  skill  gaps.  The  research  provides recommendations  for  mitigating  negative  effects  and  ensuring  a  fair  transition  for workers affected by AI advancements.